Ambulatory blood pressure measurements in mid-pregnancy and development of hypertensive pregnancy disorders. (May 2014) - Bhide, Amarnath; Sankaran, Srividhya; Moore, Jessica; Khalil, Asma; Furneaux, Eleanor
<x xml:space="preserve">Abstract</x> Objective: To explore if blood pressure (BP) readings over 24 h is a useful addition to uterine artery Doppler to screen for hypertensive disorders. Methods: In a prospective observational study, we invited nulliparous women with abnormal and normal uterine artery Doppler but normal BP at the time of their routine anomaly scan. BP was measured by the woman using automated apparatus at five specified time intervals over 24 h at 22–24 weeks. Pregnancy outcome was retrieved from delivery suite records, discharge summaries, and letters to general practitioners if necessary. Logistic regression was used to explore the contribution of uterine artery Doppler and BP measurements towards the development of pre-eclampsia. Results: Data were available from 52 women with abnormal and 48 women with normal uterine artery Doppler. Thirteen women developed hypertension in pregnancy. Significant difference was found in the BP of women who did or did not develop hypertensive disorders. BP recordings showed the diurnal variation. Both uterine artery Doppler mean PI and BP showed significant correlation with future development of hypertension. Conclusions: Women can self-measure BP at home. BP readings show diurnal variation. There are significant differences in BP of women who do and do not develop hypertension later in the pregnancy. Use of home BP monitoring over 24 h of the day in mid-pregnancy is unlikely to add to the use of uterine artery Doppler and a one-off BP reading for future development of hypertension in pregnancy.